BANK DECISION FACTORS ANALYSIS IN GIVING CREDIT SMALL MEDIUM ENTERPRISES (SMEs) (Case Study at PT. Bank Rakyat Indonesia (Persero) Tbk - Yuda, Amanda Dhani Previa (Jurnal Administrasi Bisnis, 2013)
The result is gathered from PT. Bank BRI Unit Office Klojen Malang’s decision in giving out the credit for Small Medium Enterprises (SMEs). In cases where that factor is a variable of credit collateral value amounts 0,000 < Alpha score (0,05) which can not refuse Ho, that there is a significant influence between credit collateral value toward the decision of giving the credit for Small Medium Enterprises (SMEs). The variable types of business amounts 0,004 < Alpha score (0,05), then can refuse Ho, that there is a significant influence between the variable types of business toward the decision of giving the credit for Small Medium Enterprises (SMEs). Firm age variable itself amounts 0,005 < Alpha score (0,05), then can refuse Ho, that there is a significant influence between firm age variable toward the decision of giving the credit for Small Medium Enterprises (SMEs). Sales revenue variable amounts 0,007 < Alpha score (0,05), which can refuse Ho, that there is a significant influence between sales revenue variable toward the decision of giving the credit for Small Medium Enterprises (SMEs). Net income variable amounts 0,004 < Alpha score (0,05), which can refuse Ho, that there is a significant influence between net income variable toward the decision of giving the credit for Small Medium Enterprises (SMEs). Keywords: 5 variables, bank’s decision in giving the credit, logistic regression